High-performance strontium permanent ferrite and preparation process thereof

CN122958162APending Publication Date: 2026-10-23ANHUI ONE MAGNET ELECTRONIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611069504.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0008]本发明的目的在于提供一种高性能锶永磁铁氧体及其制备工艺,以解决La-Co掺杂锶永磁铁氧体在高致密化烧结过程中容易发生晶粒异常长大,进而导致矫顽力和方形度下降的问题

Benefits of technology

[0022]与现有技术相比,本发明提供了一种高性能锶永磁铁氧体及其制备工艺,具备以下有益效果:通过La-Co-Al-Ca掺杂的SrFe12O19主相与Ca-Si-B富集晶界相协同作用,使锶永磁铁氧体在保持较高致密度的同时抑制异常晶粒长大,从而兼顾高Br、高Hcj和高(BH)max。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958162A_ABST
    Figure CN122958162A_ABST
Patent Text Reader

Abstract

The application discloses a high-performance strontium permanent magnet ferrite and a preparation process thereof, and belongs to the technical field of permanent magnet ferrite materials. 12 O 19 The main phase of the La-Co-Al-Ca doped SrFe 1‑x‑ CaLa x Fe 12‑x‑ zCo x AlzO 19 , wherein x is 0.08-0.25, y is 0.01-0.06, and z is 0.02-0.12; and a Ca-Si-B enriched grain boundary phase located between the main phase crystal grains; the average grain size of the main phase crystal grains of the high-performance strontium permanent magnet ferrite is 0.65-1.20 microns, the proportion of the number of abnormal grains with a grain size greater than 2.5 microns is not more than 5%, and the relative density of a sintered body is not less than 95.0%; the La-Co-Al-Ca doped SrFe 12 O 19 main phase and the Ca-Si-B enriched grain boundary phase synergistically act, so that the strontium permanent magnet ferrite can inhibit abnormal grain growth while maintaining high density, and thus high Br, high Hcj and high (BH)max are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of permanent magnet ferrite material technology, specifically relating to a high-performance strontium permanent magnet ferrite and its preparation process. Background Technology

[0002] Strontium permanent magnet ferrites belong to the hexagonal M-type ferrite material category. They possess advantages such as wide availability of raw materials, low cost, good corrosion resistance, high chemical stability, and suitability for large-scale sintering production. They are widely used in automotive motors, home appliance motors, loudspeakers, magnetic separation equipment, and sensors. With the development of miniaturized and high-efficiency motors, higher requirements are placed on the remanence (Br), intrinsic coercivity (Hcj), maximum energy product (BH)max, and squareness (Hk / Hcj) of strontium permanent magnet ferrites.

[0003] In existing technologies, to improve the magnetic properties of strontium permanent magnet ferrites, La-Co composite doping is typically used to dope SrFe. 12 O 19 The main phase undergoes modification. La³ + Partially replaces Sr² + Co² + Partially replaces Fe³ + Afterwards, it can improve the anisotropy of magnetocrystalline materials and increase the coercivity and remanence of the material; at the same time, an appropriate amount of CaO helps to densify the magnet by sintering, thereby increasing the remanence and maximum magnetic energy product of the magnet.

[0004] However, in high-performance La-Co doped strontium ferrite systems, due to the reduced main phase formation temperature and enhanced grain boundary migration ability, rapid or abnormal grain growth is prone to occur during subsequent sintering. Excessively large grains reduce the resistance required for domain reversal, leading to a decrease in intrinsic coercivity. Lowering the sintering temperature to suppress grain growth results in insufficient density, making it difficult to improve remanence and maximum energy product.

[0005] Therefore, a specific and objective technical contradiction exists in La-Co doped high-performance strontium ferrites: on the one hand, a high degree of sintering densification is required to obtain high Br and high (BH)max; on the other hand, abnormal grain growth needs to be suppressed to maintain high Hcj and high squareness. This problem is not universally present in all ordinary strontium ferrites, but rather a more prominent issue of process stability under conditions of high-performance La-Co doping, high densification sintering, and fine grain control.

[0006] Existing technologies also include methods to improve the properties of strontium ferrite by adding additives such as SiO2, CaCO3, and Al2O3. However, these methods often involve mixing the additives into powders, resulting in uneven distribution and the potential formation of enriched or coarse second phases in localized areas, leading to unstable grain boundary control. While adding CaO alone can improve sintering densification, it can also promote grain growth, causing a decrease in Hcj and squareness. Adding SiO2 alone can suppress grain growth, but insufficient sintering densification leads to a decrease in Br and (BH)max. Although the Ca-Si binary system can balance densification and grain suppression to some extent, it still has shortcomings in terms of grain boundary wettability, glass phase continuity, and squareness of the demagnetization curve.

[0007] Furthermore, existing single-stage sintering processes struggle to simultaneously achieve densification and grain suppression. While higher-temperature single-stage sintering easily yields higher density, it also results in significant abnormal grain growth. Conversely, lower-temperature single-stage sintering produces finer grains, but the sintered body's relative density is insufficient, leading to lower remanence and maximum energy product. Therefore, developing a strontium permanent magnet ferrite capable of suppressing abnormal grain growth under high density conditions, while simultaneously achieving high remanence, high coercivity, high maximum energy product, and high squareness, along with its fabrication process, is of significant practical importance. Summary of the Invention

[0008] The purpose of this invention is to provide a high-performance strontium permanent magnet ferrite and its preparation process, so as to solve the problem that La-Co doped strontium permanent magnet ferrite is prone to abnormal grain growth during high-density sintering, which leads to a decrease in coercivity and squareness.

[0009] The high-performance strontium permanent magnet ferrite and its preparation process of the present invention belong to the same inventive concept, and are both proposed to control grain growth, improve sintering density and improve magnetic properties by synergistic control of La-Co-Al-Ca doped main phase and Ca-Si-B enriched grain boundary phase.

[0010] To achieve the above objectives, the present invention provides the following technical solution: a high-performance strontium permanent magnet ferrite comprising La-Co-Al-Ca doped SrFe 12 O 19 The hexagonal ferrite main phase has the general chemical formula Sr. 1-x- Ca La x Fe 12-x- zCo x AlzO 19Where x is 0.08-0.25, y is 0.01-0.06, and z is 0.02-0.12; and Ca-Si-B enriched grain boundary phase located between the main phase grains; the average grain size of the main phase grains of the high-performance strontium permanent magnet ferrite is 0.65-1.20 μm, the proportion of abnormal grains with a grain size greater than 2.5 μm does not exceed 5%, and the relative density of the sintered body is not less than 95.0%.

[0011] Furthermore, x is 0.12-0.22 and z is 0.05-0.10, so that the high-performance strontium permanent magnet ferrite can achieve a balance between high remanence and high coercivity.

[0012] Furthermore, the Ca-Si-B enriched grain boundary phase includes an amorphous glass layer that is continuously or semi-continuously distributed between the main phase grains, and the thickness of the amorphous glass layer is 2-15 nm.

[0013] Furthermore, the orientation degree of the high-performance strontium permanent magnet ferrite is at least 0.85, preferably not less than 0.88; the squareness Hk / Hcj is at least 0.85, preferably not less than 0.88.

[0014] Furthermore, the high-performance strontium permanent magnet ferrite has a remanence Br of 420-455 mT at 20-25℃, an intrinsic coercivity Hcj of 330-430 kA / m, and a maximum energy product (BH)max of 33-39 kJ / m³.

[0015] This invention also provides a process for preparing high-performance strontium permanent magnet ferrite, comprising the following steps: Step 1: According to the main phase chemical formula Sr 1-x- Ca La x Fe 12-x- zCo x AlzO 19 Weigh out iron source, strontium source, calcium source, lanthanum source, cobalt source and aluminum source, where x is 0.08-0.25, y is 0.01-0.06 and z is 0.02-0.12. Wet mix, dry and pre-calcine the above raw materials to obtain a pre-calcined material containing La-Co-Al-Ca doped strontium ferrite main phase. Step 2: After crushing the pre-sintered material, wet fine grinding is performed, and calcium-silicon-boron composite grain boundary coating liquid is added in the later stage of wet fine grinding to form a composite coating layer containing Ca, Si and B on the surface of the pre-sintered material particles, so as to obtain magnetic slurry for orientation molding. Step 3: The magnetic slurry for orientation molding is placed in a magnetic field and wet-pressed to obtain anisotropic strontium ferrite preform; Step 4: The anisotropic strontium ferrite preform is sintered in two stages. First, the temperature is raised to a first sintering temperature of 1150-1230℃ and held to promote densification. Then, the temperature is lowered to a second sintering temperature of 1090-1170℃ and held to suppress abnormal grain growth. After cooling, high-performance strontium permanent magnet ferrite is obtained.

[0016] Further, the iron source is iron oxide red, ultrapure magnetite concentrate oxide powder, or a mixture of the two; the strontium source is strontium carbonate; the calcium source is one or more of calcium carbonate, calcium citrate, or calcium hydroxide; the lanthanum source is lanthanum oxide or lanthanum carbonate; the cobalt source is one or more of cobalt oxide, cobalt tetroxide, or cobalt carbonate; and the aluminum source is one or more of aluminum oxide, boehmite, or aluminum nitrate.

[0017] Furthermore, in step one, the solid content of the wet mixing is 45-65 wt%, the wet mixing time is 4-16 h, the drying temperature is 100-130 ℃, the pre-calcination temperature is 1120-1180 ℃, and the pre-calcination time is 1-5 h.

[0018] Further, the calcium-silicon-boron composite grain boundary coating solution is prepared by the following method: calcium citrate or calcium nitrate is dissolved in deionized water, silica sol or tetraethyl orthosilicate hydrolysate is added, and boric acid is added. The mixture is stirred for 30-90 minutes at a pH of 7.5-9.0 and a temperature of 25-45℃ to obtain the calcium-silicon-boron composite grain boundary coating solution. Specifically, based on 100 parts by weight of the pre-burned material, the amount of CaO added to the calcium-silicon-boron composite grain boundary coating solution is 0.12-0.45 parts, the amount of SiO2 added is 0.10-0.40 parts, and the amount of B2O3 added is 0.01-0.08 parts, and the mass ratio of CaO to SiO2 is 0.8-1.6:1.

[0019] Furthermore, in step two, the wet fine grinding is carried out in two stages. In the first stage, the particles in the slurry are ground until the D50 is 0.80-1.20μm. In the second stage, after adding the calcium-silicon-boron composite grain boundary coating liquid, the particles are ground until the D50 is 0.55-0.85μm and the D90 is no greater than 1.50μm.

[0020] Furthermore, in step three, the orientation magnetic field strength applied during wet pressing is 800-1300 kA / m, and the molding pressure is 35-80 MPa.

[0021] Furthermore, in step four, the first sintering temperature is preferably 1170-1210℃, and the holding time is 5-25 min; the second sintering temperature is preferably 1110-1150℃, and the holding time is 1.5-4 h; during the cooling process, the cooling rate in the range of 950-800℃ is 0.5-1.5℃ / min.

[0022] Compared with existing technologies, this invention provides a high-performance strontium permanent magnet ferrite and its preparation process, which has the following beneficial effects: SrFe2 doped with La-Co-Al-Ca 12 O 19 The main phase and the Ca-Si-B enriched grain boundary phase work together to suppress abnormal grain growth while maintaining high density in the strontium permanent magnet ferrite, thus achieving a balance of high Br, high Hcj and high (BH)max.

[0023] This invention involves adding a calcium-silicon-boron composite grain boundary coating solution after the wet fine grinding process. This allows the Ca, Si, and B components to preferentially distribute on the surface of the pre-sintered particles, forming a continuous or semi-continuous Ca-Si-B enriched grain boundary phase during sintering. Compared to conventional powder mixing methods, this approach improves the uniformity of grain boundary control and reduces local over-sintering and coarse second phases.

[0024] This invention employs a Ca-Si-B ternary composite grain boundary system. Compared to adding CaO or SiO2 alone, it can utilize the Ca component to promote sintering densification, utilize the Si component to inhibit abnormal grain growth, and improve the low-temperature wettability of grain boundaries and the continuity of amorphous glass layers through the B component, thereby improving the squareness and batch stability of the magnet.

[0025] This invention employs a two-stage sintering process. The first sintering temperature is held for a short time to promote particle neck growth and sintering densification. Then, the temperature is lowered to the second sintering temperature and held for a long time, which helps to suppress grain boundary migration and abnormal grain growth, thereby improving the coercivity and squareness of the magnet.

[0026] This invention introduces an appropriate amount of Al to replace Fe sites, which can improve the magnetocrystalline anisotropy field and suppress excessive grain growth; when combined with La-Co doping, Hcj can be further improved at a higher remanence level, avoiding grain growth and coercivity reduction caused by pure La-Co doping.

[0027] This invention helps stabilize the amorphous glass layer at grain boundaries and reduce local stress concentration by controlling the cooling rate in the 950-800℃ range, thereby improving the squareness of the demagnetization curve and further increasing Hk / Hcj.

[0028] The preparation process of this invention uses common ferrite raw materials, wet ball milling, wet pressing magnetic field orientation, and air sintering. It is suitable for implementation in existing strontium ferrite production lines, and is especially suitable for implementation in modern tunnel kilns or box furnaces equipped with precision temperature control systems. The wet pressing equipment is preferably capable of providing a stable and uniform high-orientation magnetic field to ensure the magnet orientation degree and batch consistency. Attached Figure Description

[0029] Figure 1These are scanning electron microscope images of the strontium permanent magnet ferrites obtained in Example 3, Comparative Example 5, and Comparative Example 6. Figure 2 The TEM-EDS line scan distribution of Ca, Si, and B elements at the grain boundaries of the strontium permanent magnet ferrite obtained in Example 3 and Comparative Example 2 are shown. Figure 3 The above are statistical diagrams showing the grain size distribution of the strontium permanent magnet ferrites obtained in Example 3, Comparative Example 3, and Comparative Example 4. Figure 4 This is a comparison chart of the demagnetization curves of the strontium permanent magnet ferrites obtained in Example 3, Comparative Example 8, and Comparative Example 9. Detailed Implementation

[0030] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only for illustrating the present invention and are not intended to limit the scope of protection of the present invention. Other implementation methods obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.

[0031] Please see Figures 1-4 This invention provides a technical solution for high-performance strontium permanent magnet ferrite and its preparation process: Unless otherwise specified in the following examples and comparative examples, the iron source used is iron oxide red with an Fe2O3 content of not less than 99.0 wt%, the strontium source is industrial-grade strontium carbonate, the lanthanum source is lanthanum oxide, the cobalt source is cobalt tetroxide, the aluminum source is aluminum oxide, the calcium source is calcium carbonate and calcium nitrate, the silicon source is silica sol, and the boron source is boric acid. The wet ball milling media is deionized water, and the dispersant is ammonium polyacrylate, with a dispersant dosage of 0.35 wt% of the total raw material mass.

[0032] The process of this invention can be implemented in laboratory box furnaces, pilot-scale box furnaces, or continuous tunnel kilns equipped with multi-temperature zone precision temperature control systems. For industrial-scale implementation, the short-term holding section at the first sintering temperature, the long-term holding section at the second sintering temperature, and the controlled cooling section at 950-800℃ should be set as independent temperature zones to ensure stable sintering curves. The wet-press magnetic field forming equipment preferably has a magnetic field uniformity control function, and the magnetic field strength fluctuation in the forming zone should preferably not exceed ±5% of the set value.

[0033] Example 1 According to the main phase chemical formula Sr 1-x- Ca La x Fe 12-x- zCo x AlzO 19Weigh the raw materials, where x is 0.08, y is 0.01, and z is 0.02. Based on 100 parts of pre-burned material, the amount added to the calcium-silicon-boron composite grain boundary coating solution is 0.12 parts of CaO, 0.10 parts of SiO2, and 0.01 parts of B2O3.

[0034] The above raw materials were added to deionized water and a dispersant and then wet-mixed for 4 hours, with the solid content of the wet mixture controlled at 45 wt%. After mixing, the mixture was spray-dried and pre-calcined at 1120℃ for 1 hour to obtain the pre-calcined material.

[0035] After the pre-calcined material is crushed, it undergoes a first stage of wet fine grinding to achieve a particle size distribution (D50) of 1.20 μm in the slurry. Subsequently, a calcium-silicon-boron composite grain boundary coating solution is added, followed by a second stage of wet fine grinding to achieve a particle size distribution (D50) of 0.85 μm in the slurry. The resulting magnetic slurry is then wet-pressed under a 1000 kA / m orientation magnetic field and a 55 MPa molding pressure to obtain an anisotropic strontium ferrite preform.

[0036] After drying the blank, it is sintered in two stages. First, the temperature is raised to 1150℃ and held for 25 minutes, and then lowered to 1090℃ and held for 4.0 hours. During the cooling process, the cooling rate in the range of 950-800℃ is controlled at 1.5℃ / min to obtain high-performance strontium permanent magnet ferrite.

[0037] Example 2 The raw materials are weighed according to the chemical formula of the main phase, where x is 0.12, y is 0.02, and z is 0.05. Based on 100 parts of pre-burned material, the amount added to the calcium-silicon-boron composite grain boundary coating solution is 0.20 parts based on CaO, 0.16 parts based on SiO2, and 0.03 parts based on B2O3.

[0038] The above raw materials were added to deionized water and a dispersant and then wet-mixed for 7 hours, with the solid content of the wet mixture controlled at 50 wt%. After mixing, the mixture was spray-dried and pre-calcined at 1140℃ for 2 hours to obtain the pre-calcined material.

[0039] The pre-sintered material was crushed and then subjected to a first stage of wet fine grinding to achieve a particle size (D50) of 1.08 μm. Subsequently, a calcium-silicon-boron composite grain boundary coating solution was added, and a second stage of wet fine grinding was carried out to achieve a particle size (D50) of 0.78 μm. The resulting magnetic slurry was then wet-pressed under a 1000 kA / m orientation magnetic field and a 55 MPa molding pressure to obtain an anisotropic strontium ferrite preform.

[0040] After drying the blank, it is sintered in two stages. First, the temperature is raised to 1170℃ and held for 20 minutes, then lowered to 1110℃ and held for 3.2 hours. During the cooling process, the cooling rate is controlled at 1.2℃ / min in the range of 950-800℃ to obtain high-performance strontium permanent magnet ferrite.

[0041] Example 3 According to the main phase chemical formula Sr 1-x- Ca La x Fe 12-x- zCo x AlzO 19 Weigh the raw materials, where x is 0.16, y is 0.035, and z is 0.07. Based on 100 parts of pre-burned material, the amount added to the calcium-silicon-boron composite grain boundary coating solution is 0.28 parts of CaO, 0.22 parts of SiO2, and 0.05 parts of B2O3.

[0042] The above raw materials were added to deionized water and a dispersant and then wet-mixed for 10 hours, with the solid content of the wet mixture controlled at 58 wt%. After mixing, the mixture was spray-dried and pre-calcined at 1150°C for 3 hours to obtain the pre-calcined material.

[0043] The pre-calcined material was crushed and then subjected to a first stage of wet fine grinding to achieve a particle size (D50) of 1.00 μm. Subsequently, a calcium-silicon-boron composite grain boundary coating solution was added, followed by a second stage of wet fine grinding to achieve a particle size (D50) of 0.70 μm and a D90 of no more than 1.50 μm. The resulting magnetic slurry was then wet-pressed under a 1000 kA / m orientation magnetic field and a 55 MPa molding pressure to obtain an anisotropic strontium ferrite preform.

[0044] After drying the blank, it is sintered in two stages. First, the temperature is raised to 1190℃ and held for 15 minutes, then lowered to 1130℃ and held for 2.5 hours. During the cooling process, the cooling rate is controlled at 1.0℃ / min in the range of 950-800℃ to obtain high-performance strontium permanent magnet ferrite.

[0045] TEM-EDS line scan analysis of the magnet obtained in Example 3 showed that Ca, Si, and B were enriched together at the grain boundaries between the main phase grains, forming a continuous or semi-continuous enriched layer with a thickness of about 2-15 nm. This indicates that the calcium-silicon-boron composite grain boundary coating liquid can be effectively transformed into a grain boundary regulating phase during the sintering process.

[0046] Example 4 The raw materials are weighed according to the chemical formula of the main phase, where x is 0.22, y is 0.05, and z is 0.10. Based on 100 parts of pre-burned material, the amount added to the calcium-silicon-boron composite grain boundary coating solution is 0.36 parts based on CaO, 0.30 parts based on SiO2, and 0.06 parts based on B2O3.

[0047] The above raw materials were added to deionized water and a dispersant and then wet-mixed for 13 hours, with the solid content of the wet mixture controlled at 62 wt%. After mixing, the mixture was spray-dried and pre-calcined at 1165°C for 4 hours to obtain the pre-calcined material.

[0048] The pre-sintered material was crushed and then subjected to a first stage of wet fine grinding to achieve a particle size distribution (D50) of 0.90 μm. Subsequently, a calcium-silicon-boron composite grain boundary coating solution was added, and a second stage of wet fine grinding was carried out to achieve a particle size distribution (D50) of 0.62 μm. The resulting magnetic slurry was then wet-pressed under a 1000 kA / m orientation magnetic field and a 55 MPa molding pressure to obtain an anisotropic strontium ferrite preform.

[0049] After drying the blank, it is sintered in two stages. First, the temperature is raised to 1210℃ and held for 10 minutes, then lowered to 1150℃ and held for 2.0 hours. During the cooling process, the cooling rate is controlled at 0.8℃ / min in the range of 950-800℃ to obtain high-performance strontium permanent magnet ferrite.

[0050] Example 5 The raw materials are weighed according to the chemical formula of the main phase, where x is 0.25, y is 0.06, and z is 0.12. Based on 100 parts of pre-burned material, the amount added to the calcium-silicon-boron composite grain boundary coating solution is 0.45 parts based on CaO, 0.40 parts based on SiO2, and 0.08 parts based on B2O3.

[0051] The above raw materials were added to deionized water and a dispersant and then wet-mixed for 16 hours, with the solid content of the wet mixture controlled at 65 wt%. After mixing, the mixture was spray-dried and pre-calcined at 1180℃ for 5 hours to obtain the pre-calcined material.

[0052] The pre-sintered material was crushed and then subjected to a first stage of wet fine grinding to achieve a particle size distribution (D50) of 0.80 μm. Subsequently, a calcium-silicon-boron composite grain boundary coating solution was added, and a second stage of wet fine grinding was carried out to achieve a particle size distribution (D50) of 0.55 μm. The resulting magnetic slurry was then wet-pressed under a 1000 kA / m orientation magnetic field and a 55 MPa molding pressure to obtain an anisotropic strontium ferrite preform.

[0053] After drying the blank, it is sintered in two stages. First, the temperature is raised to 1230℃ and held for 5 minutes, then lowered to 1170℃ and held for 1.5 hours. During the cooling process, the cooling rate is controlled at 0.5℃ / min in the range of 950-800℃ to obtain high-performance strontium permanent magnet ferrite.

[0054] The only difference in Comparative Example 1 is that the calcium-silicon-boron composite grain boundary coating liquid is not added during the second wet fine grinding process. The other raw material composition, wet mixing time, pre-firing regime, fine grinding particle size, wet pressing molding conditions, two-stage sintering regime and cooling regime are the same as in Example 3.

[0055] The only difference in Comparative Example 2 is that only Ca and Si are added to the composite grain boundary coating solution, and no B is added, i.e., no B2O3 component is added. All other process conditions are the same as in Example 3.

[0056] The only difference in Comparative Example 3 is that only 0.28 parts of calcium source (calculated as CaO) were added in the second wet fine grinding stage, and Si and B were not added. All other conditions were the same as in Example 3.

[0057] The only difference in Comparative Example 4 is that only 0.22 parts of silicon source (calculated as SiO2) were added in the second wet fine grinding stage, and Ca and B were not added. All other conditions were the same as in Example 3.

[0058] The only difference in Comparative Example 5 is that the sintering process was changed from two-stage sintering to single-stage high-temperature sintering, that is, directly heating to 1190°C and holding for 2.5 hours before cooling. All other conditions are the same as in Example 3.

[0059] The only difference in Comparative Example 6 is that the sintering process was changed from two-stage sintering to single-stage low-temperature sintering, that is, directly heating to 1130°C and holding for 2.5 hours before cooling. All other conditions are the same as in Example 3.

[0060] The only difference in Comparative Example 7 is that the Ca-Si-B composite grain boundary coating solution was added before the start of the first stage of wet fine grinding, instead of after the wet fine grinding stage. All other conditions were the same as in Example 3.

[0061] The only difference in Comparative Example 8 is that no aluminum source is added, i.e., z=0. The amounts of x, y, and Ca-Si-B grain boundary phases added, as well as the preparation process, are the same as in Example 3.

[0062] The only difference in Comparative Example 9 is that the cooling rate in the 950-800℃ range during the cooling process is 5.0℃ / min, and all other conditions are the same as in Example 3.

[0063] Performance testing methods 1. Phase Analysis: X-ray diffraction was used to analyze the phase composition of the magnets obtained in the examples and comparative examples. The test range was 2θ = 20-80°. The results confirmed that the samples were mainly M-type SrFe.12 O 19 Hexagonal ferrite main phase.

[0064] 2. Microstructure test: The sintered magnet was cut, inlaid, polished and hot-etched along the orientation direction. The grain morphology was observed using a scanning electron microscope. No less than 5 fields of view were randomly selected, and no less than 500 grains were counted. The average grain size of the main phase grains and the proportion of abnormal grains with a grain size greater than 2.5 μm were calculated. Figure 2 In the process, it is preferable to mark abnormal grains with arrows to distinguish them from normal grains.

[0065] 3. Grain boundary elemental distribution test: The distribution of Ca, Si, and B at the grain boundaries is analyzed using transmission electron microscopy and energy dispersive spectroscopy (EDS) line scanning or area scanning to determine whether continuous or semi-continuous Ca-Si-B enriched grain boundary phases have formed. To characterize the 2-15 nm scale grain boundary enrichment layer, the transmission electron microscopy samples are preferably prepared using focused ion beam, and high-resolution line scanning is performed in the direction perpendicular to the grain boundaries.

[0066] 4. Density Test: The Archimedes displacement method was used to test the bulk density of the sintered body, and SrFe was used as the reference value. 12 O 19 The relative density is calculated based on the theoretical density.

[0067] 5. Magnetic Performance Testing: The sintered magnets were processed into standard test samples and tested according to GB / T 3217-2022 "Magnetic Test Methods for Permanent Magnet (Hard Magnetic) Materials". Remanence (Br), intrinsic coercivity (Hcj), maximum energy product (BH)max, and demagnetization curve were measured at 20-25℃. Hk is defined as the magnetic field strength corresponding to a magnetic induction intensity of 0.9Br on the demagnetization curve, and squareness is expressed as Hk / Hcj.

[0068] 6. Temperature coefficient test: As needed, test the Br and Hcj temperature coefficients of the sample in the range of 20-100℃ according to GB / T 24270-2009 "Measurement method of temperature coefficient of magnetic properties of permanent magnet materials" to evaluate the thermal stability of the material.

[0069] 7. Orientation degree test: The orientation degree is calculated by X-ray diffraction. The degree of magnet orientation is characterized by the ratio of the intensity of the (00l) crystal plane diffraction peak in the orientation plane of the sample to the total intensity of the main diffraction peaks.

[0070] 8. Batch stability test: Using Example 3 as the preferred scheme, five independent batches of samples were prepared consecutively. Each batch used the same raw material system, the same fine grinding particle size control, the same wet pressing orientation magnetic field, and the same two-stage sintering curve. Br, Hcj, and Hk / Hcj were tested for each batch, and the mean, standard deviation, and range were calculated to evaluate the industrial repeatability of the process of this invention.

[0071] Performance test results Table 1 Performance test results of the examples and comparative examples

[0072] As shown in Table 1, Examples 1-5 all achieved a relative density of not less than 95.0%, the average grain size of the main phase was in the range of 0.65-1.20 μm, and the proportion of abnormal grains with a grain size greater than 2.5 μm did not exceed 5%, indicating that the present invention is feasible at both ends and in the middle region of the numerical range defined in the claims.

[0073] The magnet obtained in Example 3 has a Br of 448 mT, an Hcj of 401 kA / m, a (BH)max of 37.8 kJ / m³, and an Hk / Hcj of 0.93. This indicates that under the combined effects of the La-Co-Al-Ca doped main phase, the Ca-Si-B enriched grain boundary phase, the coating after fine grinding, and the two-stage sintering, it is possible to simultaneously obtain high remanence, high coercivity, and high squareness.

[0074] Compared with Example 3, Comparative Example 1, without the addition of Ca-Si-B composite grain boundary coating liquid, resulted in a magnet with a relative density decreasing to 93.0%, an abnormal grain ratio increasing to 13.5%, and Hcj decreasing to 276 kA / m. This indicates that Ca-Si-B enriched grain boundaries have a significant effect on improving density and inhibiting abnormal grain growth.

[0075] Compared with Example 3, Comparative Example 2 omitted only B2O3, and the relative density, Hcj, and Hk / Hcj of the resulting magnet were significantly reduced, indicating that the B component helps to form a grain boundary phase with better wettability, thereby improving the grain boundary continuity and the squareness of the demagnetization curve.

[0076] Compared with Example 3, Comparative Example 3, with the addition of CaO alone, although the relative density reached 95.4%, the proportion of abnormal grains increased to 8.9% and Hcj decreased to 329 kA / m. This indicates that CaO alone promotes densification but also easily promotes grain growth, making it difficult to stably obtain high coercivity.

[0077] Compared with Example 3, Comparative Example 4, which added SiO2 alone, had an average grain size of 0.88 μm and an abnormal grain ratio of 3.8%, indicating that SiO2 has a certain grain suppression effect. However, the relative density was only 93.6%, and Br and (BH)max were significantly reduced, indicating that SiO2 alone is difficult to meet the high densification requirements.

[0078] Compared with Example 3, Comparative Example 5 adopted single-stage high-temperature sintering. Although the relative density reached 97.0%, the average grain size increased to 1.85 μm, the proportion of abnormal grains increased to 18.2%, Hcj decreased to 292 kA / m, and Hk / Hcj decreased to 0.75. This shows that single-stage high-temperature sintering is difficult to simultaneously achieve densification and grain suppression.

[0079] Compared with Example 3, Comparative Example 6 adopted single-stage low-temperature sintering, with an average grain size of only 0.76 μm and an abnormal grain ratio of 1.5%. However, the relative density decreased to 92.8%, and Br and (BH)max decreased to 396 mT and 28.9 kJ / m³, respectively. This indicates that although single-stage low-temperature sintering can suppress grain growth, it is not dense enough and it is difficult to obtain high comprehensive magnetic properties.

[0080] Compared with Example 3, Comparative Example 7 added the Ca-Si-B composite grain boundary coating liquid before the start of the first stage of fine grinding. The proportion of abnormal grains in the resulting magnet increased to 9.2%, and Hcj and Hk / Hcj both decreased. This indicates that adding the composite grain boundary coating liquid in the later stage of wet fine grinding is more conducive to forming an effective coating layer on the particle surface and avoids excessive dispersion or agglomeration of the additives.

[0081] Compared with Example 3, Comparative Example 8 did not add Al. Although Br was higher, Hcj decreased significantly to 308 kA / m, and Hk / Hcj decreased to 0.81. This indicates that an appropriate amount of Al replacing Fe sites helps to improve coercivity and improve the squareness of the demagnetization curve.

[0082] Compared with Example 3, Comparative Example 9 only increased the cooling rate in the 950-800℃ range to 5.0℃ / min. The resulting magnet Br and Hcj changed little, but Hk / Hcj decreased from 0.93 to 0.86, indicating that the cooling regime defined by the present invention helps to obtain higher squareness.

[0083] Batch stability testing To verify the industrial reproducibility of the preferred process of this invention, five independent batches of samples were prepared continuously according to the formulation and process parameters of Example 3, and were designated as Example 3-1, Example 3-2, Example 3-3, Example 3-4, and Example 3-5, respectively. Each batch of samples was tested according to the magnetic property testing method described above, and the results are shown in Table 2.

[0084] Table 2. Stability data of 5 independent batches of the preferred scheme in Example 3

[0085] As shown in Table 2, the range of Br in the preferred scheme of Example 3 is 3mT, the range of Hcj is 6kA / m, and the range of Hk / Hcj is 0.02 in 5 independent batches. This indicates that the technical combination formed by wet fine grinding followed by coating, two-stage sintering and controlled cooling has good process stability and repeatability, and is suitable for industrial-scale production.

[0086] The wet mixing, spray drying, pre-calcination, wet fine grinding, wet pressing magnetic field forming, and air sintering processes employed in this invention are all commonly used or easily configured process units in the production of strontium permanent magnet ferrites, eliminating the need for high-cost equipment such as vacuum melting and hot pressing deformation. During industrialization, the key control points mainly include the following aspects: 1. During the raw material mixing stage, the La, Co, Al and Ca components should be evenly dispersed to avoid local enrichment that could lead to abnormal grain growth.

[0087] 2. During the wet fine grinding stage, the particle size of the first and second stages of fine grinding should be controlled so that the composite grain boundary coating liquid is preferentially distributed on the particle surface in the later stage of fine grinding, rather than completely destroying the coating structure under long-term strong shear.

[0088] 3. During the wet pressing magnetic field forming stage, forming equipment with stable and uniform magnetic field strength should be used. The preferred orientation magnetic field strength is 800-1300 kA / m to ensure that the magnet orientation degree is not less than 0.85.

[0089] 4. During the sintering stage, a modern tunnel kiln or box furnace equipped with a precision temperature control system is preferred. The first sintering temperature is held for a short time, the second sintering temperature is held for a long time, and the temperature is controlled and cooled in the range of 950-800℃ through programmed temperature control.

[0090] 5. For cost-sensitive applications, a lower La-Co-Al doping amount and a lower Ca-Si-B grain boundary phase addition amount can be used to achieve a cost-performance balance; for high-performance motors or compact magnetic components, the preferred schemes near Example 3 or Example 4 can be used to improve the magnetic performance per unit volume and reduce system-end material consumption.

[0091] In summary, this invention solves the problem of decreased coercivity and squareness caused by abnormal grain growth in La-Co-doped high-performance strontium ferrite under high-density sintering conditions by employing the synergistic effects of La-Co-Al-Ca doped main phase, Ca-Si-B enriched grain boundary phase, wet fine grinding followed by coating, a two-stage sintering process, and controlled cooling. This results in a high-performance strontium permanent magnet ferrite exhibiting high Br, high Hcj, high (BH)max, and high Hk / Hcj. Furthermore, multiple batch stability data demonstrate that the process of this invention has good repeatability and industrial feasibility.

Claims

1. A high-performance strontium permanent magnet ferrite, characterized in that, include: La-Co-Al-Ca doped SrFe 12 O 19 The hexagonal ferrite main phase has the general chemical formula Sr. 1-x- Ca La x Fe 12-x- zCo x AlzO 19 Where x is 0.08-0.25, y is 0.01-0.06, and z is 0.02-0.12; And the Ca-Si-B enriched grain boundary phase located between the main phase grains; The high-performance strontium permanent magnet ferrite has an average main phase grain size of 0.65-1.20 μm, an abnormal grain size greater than 2.5 μm with a proportion not exceeding 5%, and a relative density of the sintered body not less than 95.0%.

2. The high-performance strontium permanent magnet ferrite according to claim 1, characterized in that, The x is 0.12-0.22, the z is 0.05-0.10, the remanence Br of the high-performance strontium permanent magnet ferrite at 20-25℃ is not less than 440mT, and the intrinsic coercivity Hcj is not less than 380kA / m.

3. The high-performance strontium permanent magnet ferrite according to claim 1, characterized in that, The Ca-Si-B enriched grain boundary phase includes an amorphous glass layer that is continuously or semi-continuously distributed between the main phase grains, and the thickness of the amorphous glass layer is 2-15 nm.

4. The high-performance strontium permanent magnet ferrite according to claim 1, characterized in that, The orientation degree of the high-performance strontium permanent magnet ferrite is at least 0.85, preferably not less than 0.88; the squareness Hk / Hcj is at least 0.85, preferably not less than 0.

88.

5. The high-performance strontium permanent magnet ferrite according to claim 1, characterized in that, The high-performance strontium permanent magnet ferrite has a maximum energy product (BH)max of 33-39 kJ / m³ at 20-25℃, and the aspect ratio of the main phase grains is 1.2-2.

8.

6. The high-performance strontium permanent magnet ferrite according to claim 1, characterized in that, Based on the total mass of the high-performance strontium permanent magnet ferrite, the CaO content is 0.12-0.45wt%, the SiO2 content is 0.10-0.40wt%, the B2O3 content is 0.01-0.08wt%, and the mass ratio of CaO to SiO2 is 0.8-1.6:

1.

7. The high-performance strontium permanent magnet ferrite according to claim 1, characterized in that, The high-performance strontium permanent magnet ferrite has a remanence Br of 420-455 mT at 20-25℃ and an intrinsic coercivity Hcj of 330-430 kA / m. Under the condition of having the Ca-Si-B enriched grain boundary phase, the proportion of abnormal grains with a particle size greater than 2.5 μm does not exceed 3%.

8. A process for preparing high-performance strontium permanent magnet ferrite, comprising a method for manufacturing the high-performance strontium permanent magnet ferrite as described in any one of claims 1-7, characterized in that, Includes the following steps: Step 1: According to the main phase chemical formula Sr 1-x- Ca La x Fe 12-x- zCo x AlzO 19 Weigh out iron source, strontium source, calcium source, lanthanum source, cobalt source and aluminum source, where x is 0.08-0.25, y is 0.01-0.06 and z is 0.02-0.

12. Wet mix, dry and pre-calcine the above raw materials to obtain a pre-calcined material containing La-Co-Al-Ca doped strontium ferrite main phase. Step 2: After crushing the pre-sintered material, wet fine grinding is performed, and calcium-silicon-boron composite grain boundary coating liquid is added in the later stage of wet fine grinding to form a composite coating layer containing Ca, Si and B on the surface of the pre-sintered material particles, so as to obtain magnetic slurry for orientation molding. Step 3: The magnetic slurry for orientation molding is placed in a magnetic field and wet-pressed to obtain anisotropic strontium ferrite preform; Step 4: The anisotropic strontium ferrite preform is sintered in two stages. First, the temperature is raised to a first sintering temperature of 1150-1230℃ and held to promote densification. Then, the temperature is lowered to a second sintering temperature of 1090-1170℃ and held to suppress abnormal grain growth. After cooling, high-performance strontium permanent magnet ferrite is obtained.

9. The preparation process of a high-performance strontium permanent magnet ferrite according to claim 8, characterized in that, In step one, the solid content of the wet mixing is 45-65 wt%, the wet mixing time is 4-16 h, the drying temperature is 100-130 ℃, the pre-calcination temperature is 1120-1180 ℃, and the pre-calcination time is 1-5 h. The calcium-silicon-boron composite grain boundary coating solution was prepared by the following method: Calcium citrate or calcium nitrate is dissolved in deionized water, silica sol or tetraethyl orthosilicate hydrolysate is added, and then boric acid is added. The mixture is stirred for 30-90 minutes at a pH of 7.5-9.0 and a temperature of 25-45℃ to obtain a calcium-silicon-boron composite grain boundary coating solution. Specifically, based on 100 parts by weight of the pre-burned material, the amount of CaO added to the calcium-silicon-boron composite grain boundary coating solution is 0.12-0.45 parts, the amount of SiO2 added is 0.10-0.40 parts, and the amount of B2O3 added is 0.01-0.08 parts, and the mass ratio of CaO to SiO2 is 0.8-1.6:

1.

10. The preparation process of a high-performance strontium permanent magnet ferrite according to claim 8, characterized in that, In step two, the wet fine grinding is carried out in two stages. In the first stage, the particles in the slurry are ground until the D50 is 0.80-1.20μm. In the second stage, the calcium-silicon-boron composite grain boundary coating liquid is added and the particles are ground until the D50 is 0.55-0.85μm and the D90 is no greater than 1.50μm. In step three, the orientation magnetic field strength applied during wet pressing is 800-1300 kA / m, and the molding pressure is 35-80 MPa. In step four, the first sintering temperature is preferably 1170-1210℃, and the holding time is 5-25 min; the second sintering temperature is preferably 1110-1150℃, and the holding time is 1.5-4 h; during the cooling process, the cooling rate in the range of 950-800℃ is 0.5-1.5℃ / min, so as to obtain a high-performance strontium permanent magnet ferrite with a squareness Hk / Hcj of not less than 0.92.